Adhesion of water droplets by low voltage electrowetting on a superhydrophobic surface of a 3C-SiC nanorod network. (14th December 2015) - Khan, Afzal; Sohail, Shiraz; Jacob, Chacko
Abstract: Adhesion state of a liquid droplet on the superhydrophobic surfaces can be tuned by electrowetting and can be exploited for various applications in microfluidics, lab on chip and biotechnology, etc. Silicon carbide (SiC) can be used for these kinds of studies due to its high chemical and mechanical stability in harsh environment conditions. In this work, a low dc voltage irreversible electrowetting using a deionized water droplet on superhydrophobic hierarchical Au/Pd nanostructures coated 3C-SiC nanorod surface is demonstrated. Strong adhesion of the water droplet to the surface was achieved by changing its adhesion state from low to high and then very high by electrowetting, thereby changing the contact angle from 160° to 75°. The first irreversible transition of water droplet from Cassie regime to Wenzel regime occurred at 16 V due to the drastic increase of the work of adhesion which was found to be 10 times that of the initial value. Finally, the work of adhesion was increased about 20 times its initial value by increasing the applied voltage up to 24 V.